Barnets bästa vid assisterad befruktning: - bedömning av föräldrapotential vid behandling med och utan donerade könsceller - Lind, Judith (Socialvetenskaplig tidskrift, 2023)
The best interests of the child in assisted reproduction – assessments of parent potential in treatment with autologous and donor gametes Considerations of the welfare of the intended child in assisted reproduction include the assessment of candidates’ capacity to care for the child. Swedish legislation prescribes the evaluation of candidates’ psychological and social circumstances only when gametes from a donor are used for treatment. However, accounts of the evaluation process by fertility clinic staff indicate that candidates’ social and psychological circumstances are also considered in non-donor treatment. While legislation demands that a professional behavioural scientist is involved in the assessment for donor treatment, this is not the case for non-donor treatment. Candidates for non-donor treatment are reported as being evaluated by a counsellor only if they attract the negative attention of clinic staff through self-disclosed information or their behaviour during visits to the clinic. The outcome is an evaluation process in non-donor treatment that is non-transparent and therefore unpredictable for candidates. This article is based on focus group discussions with fertility clinic staff at four public clinics in Sweden.